The Effect of Financial Constraint on Farmers’ Health: Evidence from Rural China. - Orach, Henry; Pu, Chen; Qianling, Shen; Shiying, Wei; Ssewajje, Hassan; Wigmore, Rosie (Advances in Social Sciences Research Journal, 2021)
Health is an important tool to farmers. However, percentage of farmers are unable to obtain good health due to inadequate capital and inadequate access to credit from financial institutions. Using China’s rural household income survey (CHIP) database conducted in 2014, this study contributes to the literatures by analyzing the effect of credit rationing on rural farmers’ health status. Ordered probit model was used to evaluate the impact of credit rationing on farmers’ health status. Credit rationing was found to play the negative role of hindering rural farmers from accessing good health status. This study definitely answers the question regarding the negative effect of credit rationing on the health status of rural household farmers. Further study to establish causal relationships using time-variants/panel datasets.